Pengembangan E-Handout Berbasis Flip HTML5 Materi Sistem Gerak Manusia Menggunakan Model PBL untuk Siswa Kelas XI SMA - Rudiah Damayanti; Aminuddin Prahatama Putra (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
Biology learning on human movement system material still faces obstacles in the learning process. The limitations of teaching materials used in terms of appearance and content are one of the factors that affect the learning process and student understanding of the material. Flip HTML5-based e-handouts are digital teaching materials that are relevant to the demands of 21st century learning. This study aims to describe the validity and readability of the development of Flip HTML5-based e-handouts of human motion system material using the PBL model for grade XI high school students. This research and development uses the 4D model, but only until the development stage. The subjects in this study were 2 experts for media validation and material validation tests, and 9 XI grade students for the readability test. The results showed that the Flip HTML5-based e-handout of human motion system material using the PBL model for grade XI high school students developed obtained a validity value of 91.92% which was classified as very valid and a readability value of 88.62% which was classified as very practical.Kata kunci: E-handout, flip html5, model 4D, PBL, sistem gerak manusia